The correlation between CRB1 variants and the clinical severity of Brazilian patients with different inherited retinal dystrophy phenotypes - Fabiana Louise Motta; Mariana Vallim Salles; Karita Antunes Costa; Rafael Filippelli-Silva; Renan Paulo Martin; Juliana Maria Ferraz Sallum (Scientific Reports, 2017)
Abstract Inherited retinal dystrophies are characterized by progressive retina degeneration and mutations in at least 250 genes have been associated as disease-causing. CRB1 is one of many genes analyzed in molecular diagnosis for inherited retinal dystrophy. Crumbs homolog-1 protein encoded by CRB1 is important for cell-to-cell contact, polarization of epithelial cells and the morphogenesis of photoreceptors. Pathogenic variants in CRB1 lead to a huge variety of phenotypes ranging from milder forms of inherited retinal dystrophy, such as retinitis pigmentosa to more severe phenotypes such as Leber congenital amaurosis. In this study, seven novel likely-pathogenic variants were identified: four missense variants (p.Leu479Pro, p.Ala921Pro, p.Cys948Arg and p.Asp1031Asn), two frameshift deletions (c.2536_2542del7 and c.3460_3461delTG) and one frameshift indel variant (c.276_294delinsTGAACACTGTAC). Furthermore, two patients with cone-rod dystrophy due to mutations in CRB1 were reported, supporting previous data, in which mutations in CRB1 can also cause cone-rod dystrophy. Finally, our data suggested there was a direct relation between phenotype severity and the mutation effect on protein functionality in 15 Brazilian CRB1 patients.